Emotion and gender in local anti-austerity activist cultures - Craddock, Emma (2017)
While large-scale studies of European anti-austerity movements exist, there is a need for in-depth, ‘thick description’ of anti-austerity activist cultures which explores the sustaining as well as motivating factors for political engagement. Furthermore, it is important to pay attention to differences, including gendered differences, within counterhegemonic movements to highlight the power imbalances that exist. This thesis utilises a cultural and affective approach combined with a gender lens to explore the lived and felt experiences of political participation and the gendered dimension of these. It contributes to developing a cultural and feminist approach to studying movements that takes account of emotion and gender by developing an in-depth understanding of a local anti-austerity activist culture.